Handbook of meat and meat processing - Aalhues, J. L.; Hui, Y. H. [ (Yiu H.)] (CRC Press, 2012)
Featuring twenty new chapters reflecting current interest and updating safety and quality standards and regulations, this second edition of an industry reference covers state of the art science, technology, and applications of meat products, by-products, and meat processing as well as worker safety, waste management, slaughtering, carcass evaluation, meat safety, and animal handling issues, both national and international. New topics include beef and raw meat preservation, Jewish and Muslim slaughter and preservation rules, the use of non-meat ingredients, and newly popular processing methods